Financial Technology Solutions for Financial Inclusion: A review and future agenda - Km. Neelam; Sonali Bhattacharya (Australasian Accounting, Business and Finance Journal, 2022)
Objective- This research aims to review the extant literature and the contribution of digital technology (DT) in financial inclusion (FI). In this study, researchers attempted to suggest some directions to policymakers towards furthering the initiatives for financial inclusion. The objectives are to explore user behaviour for technology adaptation of financial transactions. Design/ Methodology- A systematic literature review was conducted by using a method suggested by Cook and West (2012). The articles were selected between 2001 to 2020. Keywords such as ‘digital technology’ and Financial Inclusion (FI) were chosen for study. Full text articles in English language from SCOPUS, Web of Science and Google scholar were considered. A conceptual framework has been suggested based on the literature review, which can help future researchers to examine the current issues and challenges in the financial technology and digital technology field. Findings/Conclusion- The overall review of existing literature available on the topic signifies that digital technology is the driver of FI and economic growth. However, there are some gaps noted on which future studies can focus. Originality/Contribution/Value-In the literature review, research papers deal with problems, factors, and gaps in the use of digital technology. Thus, there is a need for more research on this topic. It is a unique study in the context of emerging economies.
Keywords: Digital technology; financial technology; financial inclusion; Digital payment; literature review; Mobile payment; financial literacy; conceptual framework